Hubungan antara Nilai Ankle Brachial Index dengan Kejadian Diabetic Foot Ulcer pada Penderita Diabetes Melitus Tipe 2 di RSUD Dr. Moewardi Surakarta - Rahmaningsih, Baiq Yuni, dr. Nur Hidayat, Sp. PD, dr. Iin Novita N.M, M. Sc., Sp. PD (2016)
Background: Diabetic foot ulcer (DFU) is one of chronic complications often suffered by the DM type 2 patients. The incidence of diabetic foot ulcer in the DM patients is 1-4% on the world. This complication often becomes the main cause of the case of the non-traumatic lower extremity amputation. The risk of conducting amputation in the diabetic foot ulcer sufferers is as much as tenfold up to thirtyfold even it is estimated that the incidence of foot amputation due to DFU happens every 20 seconds. The examination of ankle brachial index (ABI) is one of non invasive examinations to diagnose peripheral arterilal disease (PAD) which is one of the big causes of the occurence of DFU except neurophaty. The score of ABI can be useful in determining the level of stenosis in the artery in the lower extremity area, that is if the score ABI is found as much as <0.9, it signs PAD, therefore, a lower ABI score can increase the risk of suffering from diabetic foot ulcer. Purpose: This research aimed at knowing the correlation between the score of ankle brachial index and the incidence of diabetic foot ulcer in the DM type 2 sufferers. Method: The method of the research used is observational analytic through a cross sectional approach. The data obtained were presented in tabular, then being analyzed using Chi Square test at the significance level α=0.05. Results: The amount of diabetic foot ulcer sufferers who had a lower ABI score was as many as 10 people (32.3%) from 31 patients, meanwhile, in the non diabetic foot ulcer patients, most of them had a normal ABI score as many as 30 people (96.8%) from 31 patients. The results of data analysis obtained the value of p < 0.003 with the value of X2= and OR= 14,286 (CI95%; 1,698-120,203) Conclusion: There is a significant correlation between the score of ankle brachial index and the incidence of diabetic foot ulcer in the DM type 2 sufferers